Growth and Metabolic Syndrome (MetS) criteria in young children with classic Congenital Adrenal Hyperplasia (CAH) treated with corticosteroids (CS): Metabolic Syndrome in CAH - Abdel Meguid , Shaymaa Elsayed; Soliman, Ashraf T; De Sanctis , Vincenzo; Abougabal , Ahmed Mohamed Said; Ramadan, Magdy Abd El Fattah; Hassan, Mohamed; Hamed , Noor; Ahmed, Shayma (Acta Biomedica Atenei Parmensis, 2022)
Background: Treatment of children with congenital adrenal hyperplasia (CAH) with corticosteroids (CS) may increase the risk for developing different components of metabolic syndrome (MetS). Aim: We assessed the occurrence of cardiometabolic risk factors in children with CAH on treatment with CS since early infancy. Methods: Data of 30 children with CAH were analyzed retrospectively. They have received hydrocortisone (HC; n = 11) or prednisolone (P; n= 19) and fludrocortisone (0.1- 0.15 mg once daily) since early infancy. The different cardiometabolic criteria including blood pressure (BP), fasting glucose, low-density lipoprotein (LDL), and serum cholesterol concentrations were studied and compared with the data for 66 age-matched obese children. Results: Children with CAH on treatment for > 5 years had a high rate of obesity and overweight (60%) and short stature (23.3%), respectively. They had higher occurrences of abnormal cardio-metabolic components including high LDL and triglyceride and BP as well as increased carotid intima-media thickness (CIMT). Females had higher body mass index (BMI) and BP compared to males. The less controlled group was older and had faster linear growth compared to the controls. In the CAH group, BP and CIMT were correlated significantly with BMI-SDS and weight-standard deviation score (Wt-SDS). Neither the level of 17-hydroxy-Progesterone (17-OHP), nor the HC dose was correlated with BP, CIMT or BMI. Conclusion: These findings suggest the role played by excessive weight gain on the increased cardiometabolic risk factors in children with CAH on treatment with CS.